HEALTH WORKERS IN FAMILY HEALTH STRATEGY: A THEORETICAL REFLECTION (Fiep Bulletin - online, 2012)
Introduction - The professionals working in health services, whether in hospital care or Family Health Strategy, are exposed to occupational hazards, especially those handling biological materials, and may impact the health of workers. Purpose - To make a theoretical reflection on the health of the worker in the Family Health Strategy. Methodology - This is a theoretical reflection on the health of the worker in the Family Health Strategy based on the published literature on the subject. Results - In health services, whether in hospital care or Family Health Strategy, there are physical, chemical, biological, ergonomic, and emotional injuries, both for professionals and for patients acquired through accidents at work, because is an area where professionals are more likely to get diseases, whether incurred directly or indirectly. Many health professionals, in theory even knowing the risks, the protocols do not take precautionary measures in their daily practice and may result in accidents. Conclusion - Fighting infection in the offices of the Family Health Strategy remains a major challenge to health professionals, so it is important the adoption of biosecurity measures in order to break the chain of transmission of disease by avoiding cross-infection in the workplace.
Keywords: Occupational health; Occupational hazard; Prevention.